2013
DOI: 10.2105/ajph.2012.300899
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Medical Well Baby Visits and First Dental Examinations for Young Children in Medicaid

Abstract: Objective To examine the relationship between preventive well baby visits (WBV) and the timing of first dental examinations for young Medicaid-enrolled children. Methods The study focused on children born in 2000 and enrolled continuously in the Iowa Medicaid Program from birth to age 41 months (N=6,322). The main predictor variables were number and timing of WBV. The outcome variable was timing of first dental examinations. We used survival analysis to evaluate these relationships. Results Children with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…One article by Savage et al 12 involving Medicaidenrolled children in North Carolina has been described as providing "seminal" evidence of the effectiveness and costeffectiveness of early preventive dental care, 13 was used in a policy brief on early preventive dental care promoted by the Centers for Disease Control and Prevention, 10 and continues to be cited as evidence of cost-effectiveness of pediatric preventive dental care in public insurance programs. 14 However, that study actually found that children in the sample who received their first preventive visit before the age of 1 year (23 of 9204) showed no statistical difference in subsequent dental outcomes compared with the rest of the sample. Children who received their first preventive visit between ages 1and 2 years, or between ages 2 and 3 years, had significantly higher use of restorative and emergency dental services compared with children who had their first preventive visit at age 3 years or later.…”
Section: Discussionmentioning
confidence: 91%
“…One article by Savage et al 12 involving Medicaidenrolled children in North Carolina has been described as providing "seminal" evidence of the effectiveness and costeffectiveness of early preventive dental care, 13 was used in a policy brief on early preventive dental care promoted by the Centers for Disease Control and Prevention, 10 and continues to be cited as evidence of cost-effectiveness of pediatric preventive dental care in public insurance programs. 14 However, that study actually found that children in the sample who received their first preventive visit before the age of 1 year (23 of 9204) showed no statistical difference in subsequent dental outcomes compared with the rest of the sample. Children who received their first preventive visit between ages 1and 2 years, or between ages 2 and 3 years, had significantly higher use of restorative and emergency dental services compared with children who had their first preventive visit at age 3 years or later.…”
Section: Discussionmentioning
confidence: 91%
“…To facilitate early preventive dental visits for preschool-aged children enrolled in Medicaid, Askelson et al 46 described the introduction of a research framework among caregivers. In a recent study, Chi et al 47 highlighted the close association between well-child visits and first dental examinations among young Medicaideligible children, emphasizing the public health potential for using this avenue to improve children' s oral health. Emerging cost-effectiveness data provide additional support for interdisciplinary collaborations of dentistry with family medicine and pediatrics for screening and possible referral of children at high risk.…”
Section: Discussionmentioning
confidence: 99%
“…We included the number of active family and general practitioners and pediatricians per 1000 children in 2007, measured from the Area Resource File, because pediatric and general well-child care visits may influence dental care utilization. 26 The relationship between dentist supply and children's oral health may vary with the child's age because of changes in risk factors, including different stages of dental development, dietary and oral hygiene habits, social networks, and interactions between dentists and children. 27 Previous research has shown that the relationship between oral health and children's educational achievement and psychosocial well-being also varies with the child's age, 19 suggesting that dental care needs and effectiveness may vary with age.…”
Section: Discussionmentioning
confidence: 99%